Pan Islamism of Jamaluddin Al Afghani and as an Effort to Overcome Dynasty Politics - Asrofil Fuad; Muhamad Fajar Pramono (al-Afkar, Journal For Islamic Studies, 2024)
Dynasty politics is currently being hotly discussed in the public because Dynasty Politics is considered to be destroying the democratic system that already operates within the country. Dynastic politics must be prevented immediately because it has the potential to have a negative impact on a country's government. Jamaluddin Al Afghani is an Islamic cleric who operates in the political field. With his intelligence, he has been able to create ideas that can have a big influence on Muslims, namely Pan-Islamism. This article aims to present the idea of Pan-Islamism as a means of prevention against the continuous Politics of the Dynasty. In writing this article, the author uses a qualitative descriptive method by collecting primary and secondary data. With the idea of Pan-Islamism, it is hoped that Dynasty Politics can be prevented by using five methods, including: empowering the people in the political process, monitoring and accountability, fighting against nepotism, spreading patience and political education, and finally collaboration between movements in opposing Dynasty Politics.